2005
DOI: 10.1089/vim.2005.18.595
|View full text |Cite
|
Sign up to set email alerts
|

Role of Mucosal Immunity in Preventing Genital Herpes Infection

Abstract: The female genital tract is immunologically unique because it must be tolerant to spermatozoa, pregnancy, and vaginal flora, but also protect the host from pathogen challenge. The mucosal response to herpes simplex viruses (HSV), a major cause of genital ulcerative disease and critical co-factor in the HIV/AIDS epidemic, is complex and consists of the normally acidic vaginal environment, constitutively secreted and induced antimicrobial peptides, complement, and cellular responses mediated by epithelial and im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
35
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 87 publications
2
35
0
Order By: Relevance
“…An indirect inhibitory anti-HSV-2 effect of SLPI would support our data, since SLPI was found to exert its protective antiviral effect by interacting through ECs and not virus (70). However, the involvement of annexin II in anti-HSV-2 defense, which was important for anti-HIV-1 activity of SLPI, was ruled out (25). The observed inhibitory effect of Tr/E on HSV-2 attachment may have significant implications, since viral attachment to ECs is one of the critical steps required for subsequent fusion and entry of HSV-2 into ECs.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…An indirect inhibitory anti-HSV-2 effect of SLPI would support our data, since SLPI was found to exert its protective antiviral effect by interacting through ECs and not virus (70). However, the involvement of annexin II in anti-HSV-2 defense, which was important for anti-HIV-1 activity of SLPI, was ruled out (25). The observed inhibitory effect of Tr/E on HSV-2 attachment may have significant implications, since viral attachment to ECs is one of the critical steps required for subsequent fusion and entry of HSV-2 into ECs.…”
Section: Discussionsupporting
confidence: 82%
“…Serine protease inhibitor elafin (E) and its precursor, trappin-2 (Tr), along with secretory leukocyte protease inhibitor (SLPI) and defensins, belong to a large family of cationic antimicrobials that have been linked to endogenous mucosal protection against sexually transmitted pathogens, including HSV-2 and HIV-1 (23)(24)(25)(26). Trappin-2 and elafin (Tr/E), as well as SLPI, share the cysteine-rich fold with four disulfide bonds called the whey acidic protein (WAP) domain, involved in protease inhibition (27).…”
mentioning
confidence: 99%
“…40 Additionally, we have also detected several proteins from the histone family (H4, H2A, H2B, and H1.2). Traditionally, histones are considered to be intracellular proteins that are involved in chromatin arrangement inside the nucleus.…”
Section: Discussionmentioning
confidence: 76%
“…Differences include the commensal microbiota, IgG mainly from the circulation, and hormonal fluctuations that can modify genital immunity (4). Also, female reproductive tissues must tolerate sperm and developing fetuses and respond to sexually transmitted bacterial and viral pathogens (5). Naturally occurring Abs in uterine luminal fluid might help to protect the endometrium against microbial infections (6).…”
mentioning
confidence: 99%
“…Naturally occurring Abs in uterine luminal fluid might help to protect the endometrium against microbial infections (6). Several previous studies suggested that epithelial cells in the genital tract have a key role in Ag presentation and immune responses, although there are no distinct lymphoid structures in the genital tract (5,7). It is critical to understand the female genital tract immune system to develop strategies against such sexually transmitted infections as HSV-2, Chlamydia trachomatis, human papillomavirus, and HIV (8)(9)(10)(11).…”
mentioning
confidence: 99%